Darkling beetle as vector for Salmonella spp. and Escherichia coli in open house broiler chicken farms - Nur Husnina Abdul Wahab
This study is aimed at identifying the possibility of darkling beetle as vectors for Salmonella spp. and Escherichia coli in broiler chickens. Darkling beetle (Alphitobius diaperinus) or also known as lesser mealworm, is one of a significant pests that affects poultry production. The beetle can cause damage to the insulating materials of walls in poultry houses, poor flock performance of the chicks caused by ingestion of the beetles and possibility of serving as a vector for Salmonella spp. and Escherichia coli to broiler chickens. A total of 30 pooled samples were taken from 5 broiler open houses with 6 pooled samples from each house. Isolation of bacteria from the beetles was done from two sites, the external surface and internal content of the beetles, making the total of samples to be 60 samples. For isolation of Salmonella spp., the samples were inoculated onto Brilliant Green Agar (BGA) and Xylosine-Lysine-Deoxycolate (XLD) agar. For Escherichia coli, the samples were inoculated onto Coliform Chromogenic Agar (CCA). After isolation of bacteria, identification of bacteria was done. Out of 60 samples, Salmonella spp., was isolated from none of external surface samples, and only one from the internal content samples, which made up 1.7% of total sample. For Escherichia coli, it was isolated from two external surface samples and eight internal content samples, which made up 16.7% of total sample. The results demonstrated that there is low possibility for darkling beetle to be a vector for Salmonella spp., and rather low possibility for darkling beetle to be a vector for Escherichia coli.